Pengembangan Materi Ajar Mata Kuliah Pembelajaran Basa Jawa Berbasis Translation Bahasa Indonesia (Studi di Prodi PGMI STAI Al-Hikmah Tuban) - Ahmad Suyanto (Al Hikmah: Jurnal Studi Keislaman, 2021)
Lectures are a very pleasant thing for some active students. For passive students, lectures are a scourge themselves. For example he does not like one of the courses, so he will rarely enter. This greatly disrupts the learning climate in the classroom. The Center HotelOn the campus of the Al Hikmah Islamic School of Tuban one of them is a number of courses that are disliked by students, especially PGMI students. The course is Javanese Language Learning in MI / SD. This subject is very disliked by most students, because one of the reasons they do not understand the meaning of the Javanese language. The Javanese say, "wong jowo doesn't understand jowone" (Javanese don't understand Javanese). This is very ironic if left without any special handling will make students who are more passive to college increasingly. From the results of a survey conducted and interviews with some of the students it was found that the Javanese language learning course in MI / SD is indeed difficult, the article they do not understand the meaning of the Javanese words. The existence of this kind of research needs to be done to solve lecture problems, especially in Javanese Language Learning courses in MI / SD. Penetili raised the title Development of Teaching Material for Javanese Language Learning Subjects Based on Indonesian Language Translation to Improve Javanese Language Ability PGMI STAI Al Hikmah Tuban Students.With this research, it is expected that students will easily learn the Java Base Learning material in MI / SD. With students or prospective MI / SD teachers being familiar with the material they learned during college, they will be more confident that they will teach it later in MI / SD when they become MI / SD teachers. This research is a research and development (R & D). The product produced from this research is the development of teaching materials in Java Language Learning in MI / SD. This is in line with Sugiyono that Research and Development is research that is used to produce certain goods / products and test whether they are suitable for use or not.Therefore, this research aims to develop teaching materials for Java Language Learning in MI / SD-based Indonesian translation, so students are able to understand the meaning of Javanese vocabulary and become familiar with Javanese. The Center HotelThis research also includes the type of research development using the Four-D Model. However, the stages are limited to the development stage. While the approach used (Mixed) approach. Mixed is one of the development methods of research that utilizes two approaches namely quantitative and qualitative. The results of this study can be seen in three stages. The first stage of defining, this stage includes the beginning-end analysis stage, student analysis, concept analysis, task analysis, analysis of learning objectives. The second stage is the design, this stage begins to draft draft 1 and validation of the first draft of teaching material. The third stage of development includes revision of draft 1, validation of draft II teaching materials, revision of draft II results, limited trials, extensive trials, revision of draft III, and the final model of teaching materials (draft IV). From the development stage of teaching materials, it is obtained the results of the assessment of each validator, namely the material component and the presentation component of 95%, the linguistic component and the graphic component of 90%. And all components get a very decent category. The quality of teaching materials in terms of usage is obtained from the activities of Lecturers and Lecturer Responses with a percentage of 100%, student activities and student responses of 95% as well as the results of lectures from written tests increased by 15 points from the average pre-test score of 70 to an average average 85 at the post test. Keywords: Development of Teaching Materials, Javanese Bases based on Indonesian Language Translation, and Javanese Language Ability